The Amino-Terminal TPR Domain of Dia2 Tethers SCFDia2 to the Replisome Progression Complex - Morohashi, Hiroko; Maculins, Timurs; Labib, Karim (Current biology, 2009)
Eukaryotic cells contain multiple versions of the E3 ubiquitin ligase known as the SCF (Skp1/cullin/F box), each of which is distinguished by a different F box protein that uses a domain at the carboxyl terminus to recognize substrates [1, 2]. The F box protein Dia2 is an important determinant of genome stability in budding yeast [3–5], but its mode of action is poorly understood. Here we show that SCFDia2 associates with the replisome progression complex (RPC) that assembles around the MCM2-7 helicase at DNA replication forks [6]. This interaction requires the RPC components Mrc1 and Ctf4, both of which associate with a tetratricopeptide repeat (TPR) domain located at the amino terminus of Dia2. Our data indicate that the TPR domain of Dia2 tethers SCFDia2 to the RPC, probably increasing the local concentration of the ligase at DNA replication forks. This regulation becomes important in cells that accumulate stalled DNA replication forks at protein-DNA barriers, perhaps aiding the interaction of SCFDia2 with key substrates. Our findings suggest that the amino-terminal domains of other F box proteins might also play an analogous regulatory role, controlling the localization of the cognate SCF complexes.